NILAI-NILAI KEARIFAN BUDAYA LOKAL ORANG RIMBA (Studi pada Suku Minoritas Rimba di Kecamatan Air Hitam Provinsi Jambi) - Takiddin Takiddin (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2014)
This article was written to provide an overview of the values of local wisdom in the culture of Orang Rimba (Jungle People) in Black Water District Sarolangun Jambi Province. To obtain the data in question, the author conducted research by coducting interview, observation and study of literature. Orang Rimba have lifestyles and beliefs that are unique and different from the life of modern society. They looked at the forest as their residence. One belief of Orang Rimba is if there are people who died at their residence, then it is considered as an area harmful and they have to find a new place. This habit is called ”Melangun”. This belief is the main factor that affect the Orang Rimba not settled. Orang Rimba tribe regarded as backward, primitive and easily manipulated. However, if studied carrefully, Orang Rimba have so much values for us to learn, especially in their behavior with regards to natural preservation.